Genetic and Functional Analysis of the Styrene Catabolic Cluster of Pseudomonas sp. Strain Y2 - Velasco, Ana (American Society for Microbiology, 1998)
The chromosomal region of Pseudomonas sp. strain Y2 involved in the conversion of styrene to phenylacetate (upper catabolic pathway) has been cloned and sequenced. Four catabolic genes, styABCD, and two regulatory genes, stySR, were identified. This gene cluster when transferred to Escherichia coli W confers to this phenylacetate-degrading host the ability to grow on styrene as the sole carbon and energy source. Genes styABCD are homologous to those encoding the styrene upper catabolic pathway in Pseudomonas fluorescens ST. Northern blot analyses have confirmed that genes styABCD constitute a transcription unit. The transcription start site of the sty operon was mapped 33 nucleotides upstream of the styA translational start codon. The styS and styR genes, which form an independent transcriptional unit, are located upstream of the styABCD operon, and their gene products show high similarity to members of the superfamily of two-component signal transduction systems. The styS gene product is homologous to histidine kinase proteins, whereas the styR gene product exhibits similarity at its N-terminal domain with cluster 1 of receiver modules and at its C terminus with the LuxR/FixJ family 3 of DNA-binding domains. Expression of the catabolic operon decreased significantly in the absence of the stySR genes and was restored when the stySR genes were provided in trans in the presence of styrene, suggesting that the stySR system behaves as a styrene-inducible positive regulator of the styABCD operon. Finally, a gene encoding a phenylacetyl-coenzyme A ligase that catalyzes the first step in the phenylacetate catabolism (styrene lower catabolic pathway) has been identified upstream of the styS gene. This activity was found to be induced in Pseudomonas sp. strain Y2 cells grown on styrene but not present in cells grown on glycerol. These results strongly suggest that the genes responsible for the complete mineralization of styrene are clustered in the chromosome of Pseudomonas sp. strain Y2.